Un génocide à huis clos . A Secret Genocide - Dereims, Alexandre (Dereims, Alexandre, 2006)
To bring this alarming documentary to life, the director traveled to parts of Burma and Thailand where few Westerners are allowed. His efforts represent a brave attempt to call attention to the plight of the Karen people, an ethnic minority group that has been fighting for self-determination for decades.